Innovation of Fiqh Learning Through Talking Stick to Increase Students' Learning Motivation in Elementary Madrasahs - Fajri, Zaenol; Alviantika, Alviantika (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: Learning motivation is crucial to the process's effectiveness, particularly regarding Fiqh, a subject that requires a thorough comprehension of Islamic ideas. However, the lack of active engagement and attention to learning in class VI at Elementary Madrasahs actually indicates low learning desire among the pupils. Using the Talking Stick approach, this study seeks to increase students' motivation to learn the topic of Fiqh. Methodology: The planning, execution, observation, and reflection phases make up each of the two cycles of this Classroom Action Research (CAR) project. Fifteen seventh-grade students from Elementary Madrasahs were the study's subjects. Main Findings: The study's findings demonstrated that using the Talking Stick technique can increase students' learning enthusiasm. The average percentage of students' learning motivation in cycle I was 81.71% (good category); in cycle II, it rose to 92.65% (outstanding category). Meanwhile, the learning outcomes increased as expected, averaging 81.80 in cycle I and 86,20 in cycle 2. According to the study's findings, using the Talking Stick method can effectively increase students' motivation to learn Fiqh. Novelty/Originality of this study: According to the study, educators can use this technique as a substitute for engaging and interactive instruction while continuing to create new active learning strategies to raise the standard of instruction in the classroom.